Endogenizing growth via a lag for apprenticing - John Hartwick; Ngo Van Long (Queen's University, Department of Economics, 2010)
We take up a growth model with both skilled and unskilled labor, and a steady migration of some unskilled workers, who undertake apprenticing, to the skilled group of workers. Apprenticing involves a period of observing and thus labor output foregone. The time-out for observing represents a cost to the economy and this results in the rate of balanced growth being endogenous. We examine the balanced growth path and report on the stability of our dynamic system.
Keywords: O11; O15; J00; 330; endogenous growth; balanced growth; apprenticing; skilled and unskilled labor